2021
DOI: 10.1093/ajcn/nqaa351
|View full text |Cite|
|
Sign up to set email alerts
|

Formal maternal employment is associated with lower odds of exclusive breastfeeding by 14 weeks postpartum: a cross-sectional survey in Naivasha, Kenya

Abstract: Background In many low- and middle-income countries, improvements in exclusive breastfeeding (EBF) have stalled, delaying reductions in child mortality. Maternal employment is a potential barrier to EBF. Objectives We evaluated associations between maternal employment and breastfeeding (BF) status. We compared formally and non–formally employed mothers in Naivasha, Kenya, where commercial floriculture and hospitality industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The Kenya Ministry of Health developed guidance to facilitate the implementation of these policies (Kenya Ministry of Health, 2018). However, despite these policies and guidelines, formal employment in Naivasha is associated with a 36% lower prevalence of EBF at 14 weeks compared with informal or no employment (Ickes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Kenya Ministry of Health developed guidance to facilitate the implementation of these policies (Kenya Ministry of Health, 2018). However, despite these policies and guidelines, formal employment in Naivasha is associated with a 36% lower prevalence of EBF at 14 weeks compared with informal or no employment (Ickes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Breast milk is an essential food for infants in the first six months after birth. In addition to a variety of nutrients, breast milk also has a variety of bioactive substances, which have positive significance in enhancing immunity and promoting intellectual development of infants [ 1 , 2 ]. Breastfeeding reduces the risk of respiratory diseases and diarrhea in infants and reduces infant mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the fact that mothers without a job (formal or informal) would have the autonomy of their schedules to ensure exclusive breastfeeding for more months, while employed women needed to return to work early and would have less time to feed their children directly. It is reported that a higher proportion (by more than double) of unemployed mothers give EBF, compared to those who were employed [ 34 , 35 ]. The time offered (98 days, starting approximately 49 days before the expected date of delivery) could be insufficient, even though a maternity subsidy is provided in Peru [ 36 ].…”
Section: Discussionmentioning
confidence: 99%